The Interior World of Books, Browsing, and Collecting Inside the City - Snyder, Alison B. (Interiority, 2021)
A most desirable and collectable material object is the ubiquitous book. A bound composite of printed pages with words and images, it contains a microcosm of myriad narrative viewpoints, experiences, and imaginations. Metaphorically, a book compactly conceals a kind of interior space that protects the provocative lives of people, their character, ideas, and explorations, thus communicating different scales of interiority. Book collectors, called bibliophiles, revere and covet books as their object of desire. The bibliophile as seeker-collector-seller partakes of simple and complex transactions that essentially protect the lives of the books. This essay concentrates on two main book browsing locations within the urban context of Istanbul, Turkey, and the everyday interior spaces of the sahaf, the secondhand bookseller, who continues a tradition of selling new, pre-owned or secondhand ordinary or rare books. Its text moves between historic information and first-person narrative based on fieldwork to express and expand views of interiority theory, through reality and metaphor. The many scales of individual and collective impulses found inside the city streets and their inserted passage structures are exemplified by the significant simultaneity of the desire for the hand-held object and its hand-to-hand exchange.